Physical activity as a tool for preventing and treating depression: Lessons learned from the COVID‐19 pandemic - Raslescu, A; Guru, A; Delattre, B; Park, J; Harmer, CJ; Murphy, SE (Wiley Open Access, 2024)
Physical activity (PA) is understood to be important for the prevention and treatment of depression, however, less is known about the effects of withdrawal from PA on mood. Here we consider evidence published since the outbreak of the SARS‐CoV‐2 virus to assess the impact of the COVID‐19 pandemic on PA patterns and to evaluate whether engagement in PA in the context of the pandemic had an impact on depression vulnerability. During the initial stages of the pandemic and consequent lockdowns, there were global decreases in PA, with women, ethnic minorities, lower‐education, lower‐income, younger, and elderly people displaying more marked reductions in PA. Less PA was associated with a higher risk of experiencing moderate‐to‐severe depression symptoms, particularly for those who decreased their PA levels compared to pre‐pandemic. Both PA and sedentary behavior were independently associated with depression, such that low activity and high amounts of sitting both increased the likelihood of clinically significant symptoms. We also consider the role social connection during movement; while both in‐person and online PA can foster a sense of belonging, there is some evidence that socially distant, pandemic‐safe movement might disincentivise certain groups such as older adults and experienced exercisers from participating in PA. We conclude with several implications for prospective public health communications regarding PA, especially in the event of another global pandemic.